2017
DOI: 10.1002/iub.1605
|View full text |Cite
|
Sign up to set email alerts
|

Identification of two novel isoforms of mouse NUR77 lacking N‐terminal domains

Abstract: Nur77 is a member of nuclear receptor superfamily that acts as a transcription factor and regulates expression of multiple genes. Subcellular localization of Nur77 protein plays an important role in the survival and cell death. In this study, we have predicted and confirmed alternatively spliced two new transcripts of Nur77 gene in mouse. The newly identified transcripts have their alternatively spliced first exon located upstream of published 5'-UTR of the gene. Transcription factor binding sites in the possi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…1B ) ( 18 ). Rehman et al ( 19 ) identified two protein subtypes in mice that lack the Nur77 N-terminal domain, and the localization of these isoforms was predicted to be predominantly outside the nucleus. Therefore, N-terminal transactivation domain may be required for the transport of Nur77 from the nucleus to the cytoplasm.…”
Section: Structure Expression and Localization Of Nur77mentioning
confidence: 99%
“…1B ) ( 18 ). Rehman et al ( 19 ) identified two protein subtypes in mice that lack the Nur77 N-terminal domain, and the localization of these isoforms was predicted to be predominantly outside the nucleus. Therefore, N-terminal transactivation domain may be required for the transport of Nur77 from the nucleus to the cytoplasm.…”
Section: Structure Expression and Localization Of Nur77mentioning
confidence: 99%
“…Interestingly, H3K4me3 was also enriched at several Nr4a1 exons suggesting alternative transcription start sites 73 . We posit that activation of Nr4a1 at alternative promoters may produce Nr4a1 isoforms that lack the N-terminal transactivation domain, which has important implications on downstream target gene activation 74 . In addition, cell-type specific H3K27me3 depletion at Cartpt could establish the mechanism that confers A2a specific expression of this peptide.…”
Section: Discussionmentioning
confidence: 99%
“…The NR4A1 gene is located on chromosome 12 in humans, which encodes for a 598-residue protein (Hazel, Nathans, & Lau, 1988). It is hypothesized that the NTD permits NRFI-B translocation from the nucleus to the cytoplasm (Rehman, Sarwar, Husain, Ishqi, & Tabish, 2017). The DBD recognizes specific NGFI-B response elements (NBRE; AAAGGTCA) as a monomer and binds Nur-response elements (NurRE; TGATATTTN 6 AAATGCCA; N is any nucleotide) as a homodimer or heterodimer with either NURR1 or NOR-1.…”
Section: Nerve Growth Factor I-b (Ngfi-b/nur77/tr3 -Nr4a1)mentioning
confidence: 99%